Plasma oxysterols in drug-free patients with schizophrenia. Issue 221 (July 2022) - Guidara, Wassim; Messedi, Meriam; Naifar, Manel; Maalej, Manel; Khrouf, Walid; Grayaa, Sahar; Maalej, Mohamed; Bonnefont-Rousselot, Dominique; Lamari, Foudil; Ayadi, Fatma
Abstract: Evidence from clinical, genetic, and medical studies has shown the neuronal developmental disorder aspect of schizophrenia (SZ). Whereas oxysterols are vital factors in neurodevelopment, it is still unknown whether they are involved in the pathophysiology of SZ. The current study aims to explore the profile of oxysterols in plasma, ratio to total cholesterol (Tchol) and the association with clinical factors in patients with SZ. Forty men diagnosed with SZ and forty healthy controls matched for age and sex were included in the study. The ratios of cholestane-3β, 5α, 6β-triol, 27-hydroxycholesterol (27-OHC) and Cholestanol to Tchol increased in the schizophrenic group compared to controls. However, levels of 24S-hydroxycholesterol (24-OHC) were not significantly different between patients and controls. For the SZ patients, the plasma 24-OHC levels were positively correlated with the positive and negative syndrome total scores (PANSS) but negatively correlated with the Montreal Cognitive Assessment scores (MOCA). Moreover, the ratio Cholestanol to Tchol was negatively correlated with MOCA scores and positively correlated with PANSS general. The binary logistic regression analysis revealed that the ratio Cholestane-3β, 5α, 6β-triol/TChol could be considered as an independent risk factor for SZ. On the other hand, the receiver's operating characteristics analysis corresponding to potential biomarkers on SZ showed Areas Under the Curve (AUCs) of 82.1%; 69.7% and 77.6% for the ratio of Cholestane-3β, 5α, 6β-triol/TChol, 27-OHC/TChol and Cholestanol/TChol respectively. The relevance of Cholestane-3β, 5α, 6β-triol, 27-OHC and Cholestanol assays as biomarkers of this disease deserves further investigation. Highlights: The ratios of cholestane-3β, 5α, 6β-triol, 27-hydroxycholesterol (27-OHC) and Cholestanol to Tchol increased in the schizophrenic group (SZ) compared to controls. Levels of 24S-hydroxycholesterol (24-OHC) were not significantly different between SZ patients and controls. The binary logistic regression analysis revealed that the ratio Cholestane-3β, 5α, 6β-triol/TChol could be considered as an independent risk factor for SZ. The relevance of Cholestane-3β, 5α, 6β-triol, 27-OHC and Cholestanol assays as biomarkers of this disease deserves further investigation.